PENGGUNAAN APLIKASI WHATTSHAP DALAM PEMBELAJARAN SEJARAH DI KELAS X SMA N 4 KOTA JAMBI - Hafizhah, Rahmi; Rahim, Arif (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine how much influence the teacher's communication had in the learning process using the WhatsApp application on the learning activities of class X students on History material at State High School 4 Jambi City. This research is a descriptive quantitative study to determine the quality of learning by using the WhatsApp application in history learning at SMA Negeri 4 Jambi City. Based on the results of research that has been done regarding the use of the WhatsApp application in history learning at SMA Negeri 4 Jambi City. Based on the data from the questionnaire results, 36 students consisted of three indicators, each of which obtained a percentage of 75.10% classified as